2021
DOI: 10.1016/j.celrep.2021.109451
|View full text |Cite
|
Sign up to set email alerts
|

RalA and PLD1 promote lipid droplet growth in response to nutrient withdrawal

Abstract: Highlights d RalA and PLD1 are necessary for starvation-induced lipid droplet (LD) formation d RalA recruits PLD1 to lysosomes to promote LD accumulation during starvation d Inhibition of RalA or PLD1 prevents PLIN3 redistribution to growing LDs d PLD1 activity and PA are required for LD accumulation and PLIN3 localization on LDs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 110 publications
1
9
1
Order By: Relevance
“…Our data showed that the distribution pattern of PLIN3 did change slightly in cells expressing Sar1a, but not in cells expressing Sar1b ( Figure 3 and Figure 5 A), indicating PLIN3 could compensate for the PLIN2reduction on LD surface. Recently, PLIN3 was shown to localize to LDs in RalA-GTPase-dependent manner [ 41 ]. Thus, there may be several GTPases that regulate the localization of LD components to LDs in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the distribution pattern of PLIN3 did change slightly in cells expressing Sar1a, but not in cells expressing Sar1b ( Figure 3 and Figure 5 A), indicating PLIN3 could compensate for the PLIN2reduction on LD surface. Recently, PLIN3 was shown to localize to LDs in RalA-GTPase-dependent manner [ 41 ]. Thus, there may be several GTPases that regulate the localization of LD components to LDs in cells.…”
Section: Discussionmentioning
confidence: 99%
“…[10] NMR experiments were used to compare binding of non-lipidated peptides corresponding to the RalA and RalB HVR [10] (Figure 1A). The peptides were titrated into 15 N labelled CaM, and HSQC experiments were recorded at each titration point. These spectra report on the change in the chemical environment in the presence of the HVR peptides, which can be quantified as a chemical shift perturbation (CSP) at each CaM backbone amide.…”
Section: Rala Versus Ralb Binding To Cammentioning
confidence: 99%
“…Both Ral isoforms play a role in the cellular starvation response. [6,15] Upon nutrient withdrawal, RalA can cause the formation of lipid droplets by interacting with phospholipase D1 (PLD1). [15] This interaction does not involve the nucleotide sensitive effector binding site but is suggested to utilise the N-terminal 11 residues of RalA, [16] outside the canonical G domain.…”
Section: Functional Consequences For Mitochondrial Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations